2022
DOI: 10.1111/scs.13079
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of compassionate leadership: Adaptation and Spanish validation of the compassionate leadership self‐reported scale

Abstract: Project Longitudinal study of compassion and other professional quality of life determinants: A national level research on palliative care professionals (CompPal) [Estudio longitudinal de la compasión y otros determinantes de la calidad de vida profesional: Una investigación en profesionales de cuidados paliativos a nivel nacional (CompPal)] (RTI2018-094089-I00).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 88 publications
0
20
0
1
Order By: Relevance
“…Showing empathy (Hewison et al , 2019; Papadopoulos et al , 2022; Salminen-Tuomaala and Seppälä, 2022a; Salminen-Tuomaala and Seppälä, 2022b; Sansó et al , 2022) and having emotional intelligence (Ali and Terry, 2017; Hewison et al , 2018; Hewison et al , 2019; O'Toole et al , 2021; Papadopoulos et al , 2022; Sansó et al , 2022) are crucial factors in compassionate leadership. It was also expected that leaders would be compassionate towards professionals (Ali and Terry, 2017; López-Díaz et al , 2022; O'Toole et al , 2021; Salminen-Tuomaala and Seppälä, 2022a; Salminen-Tuomaala and Seppälä, 2022b; Sansó et al , 2022). Perceptions of not receiving empathy or being allowed to show negative feelings were also mentioned (Salminen-Tuomaala and Seppälä, 2022a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Showing empathy (Hewison et al , 2019; Papadopoulos et al , 2022; Salminen-Tuomaala and Seppälä, 2022a; Salminen-Tuomaala and Seppälä, 2022b; Sansó et al , 2022) and having emotional intelligence (Ali and Terry, 2017; Hewison et al , 2018; Hewison et al , 2019; O'Toole et al , 2021; Papadopoulos et al , 2022; Sansó et al , 2022) are crucial factors in compassionate leadership. It was also expected that leaders would be compassionate towards professionals (Ali and Terry, 2017; López-Díaz et al , 2022; O'Toole et al , 2021; Salminen-Tuomaala and Seppälä, 2022a; Salminen-Tuomaala and Seppälä, 2022b; Sansó et al , 2022). Perceptions of not receiving empathy or being allowed to show negative feelings were also mentioned (Salminen-Tuomaala and Seppälä, 2022a).…”
Section: Resultsmentioning
confidence: 99%
“…The presence and participation of the leader were expected from compassionate leadership. The leaders’ presence and participation in the work (Papadopoulos et al , 2021; Papadopoulos et al , 2022; Salminen-Tuomaala and Seppälä, 2022b; Sansó et al , 2022) was perceived as attending (Papadopoulos et al , 2022; Sansó et al , 2022), as in the physical presence of the leaders and participation in daily routines (Salminen-Tuomaala and Seppälä, 2022b). Knowing what is going on in the work unit (Sansó et al , 2022; Salminen-Tuomaala and Seppälä, 2022b) and working in cooperation with professionals (Papadopoulos et al , 2022; Sansó et al , 2022) were also perceived as important parts of the leaders’ presence and participation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several research shown that self-compassion may be acquired from childhood; thus, a number of measures were established for the young population [35,57]. In clinical practice, patients' psychological wellbeing is of great concern, caregivers may simultaneously face a variety of stressful and complex situations, the care provided to patients should be compassionate, and caregivers themselves require selfcompassion, as measured by scales such as the Compassionate Leadership Self-reported Scale [33], the Bolton Compassion Strengths Indicators [41] and the Sussex-Oxford Compassion Scales (SOCS) [24] were constructed for healthcare professional included medical students and nurses. Sinclair et al [55] and Roberts et al [54] both made conjoined attempts to place an emphasis on compassion practice for patients.…”
Section: Discussionmentioning
confidence: 99%